Magnesium-lithium composite electrolyte of rechargeable magnesium battery as well as preparation method and application of magnesium-lithium composite electrolyte
By using magnesium-lithium composite electrolyte in rechargeable magnesium batteries, the problems of low diffusion efficiency and poor cycle stability are solved, and the high energy density and excellent electrochemical performance of magnesium batteries are achieved.
Patent Information
- Application Number
- CN202411378573.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-02-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In practical applications, rechargeable magnesium batteries have problems such as low operating voltage, slow kinetic process and poor cycle stability, mainly due to the low diffusion efficiency of magnesium ions, limited selection of positive electrode materials, poor matching of electrolyte and electrodes, and the negative magnesium metal Passivation properties and other reasons.
Using magnesium-lithium composite electrolyte, the solvation structure and diffusion kinetic properties of magnesium ions are adjusted by adding electrolyte magnesium salts and lithium salt additives to organic ether solvents, and the reversibility of magnesium deposition and the cycle stability of the battery are improved. .
It significantly improves the diffusion kinetic properties of magnesium ions, broadens the selection range of positive electrode materials, reduces the dissolution/deposition overpotential of magnesium negative electrodes, and improves the cycle life and electrochemical performance of the battery.
Smart Images

Figure CN119419360A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of rechargeable magnesium batteries, and in particular to a magnesium-lithium composite electrolyte for a rechargeable magnesium battery, a preparation method thereof and an application thereof. Background Art
[0002] In recent years, non-precious metals that can produce multivalent cations (such as calcium, magnesium, and aluminum) have been widely studied as potential choices for negative electrode materials of future multivalent metal secondary batteries. Among them, rechargeable magnesium batteries are considered to have great potential in the field of multivalent ion batteries due to their high energy density, high safety, and low cost. Compared with the highly anticipated lithium-ion batteries, magnesium metal has a low electrode potential of -2.37V vs SHE, and its volumetric capacity reaches 3833mAh cm -3 , almost lithium metal (2046mAh cm -3 ). In addition, the natural abundance of magnesium in the earth's crust is about 2.3%, and it remains stable at room temperature, which provides magnesium-ion batteries with more cost-effectiveness and better safety. In addition, the magnesium negative electrode tends to form a smooth and uniform deposition layer during the electrodeposition process, effectively avoiding the nucleation and growth of dendrites, thereby further improving the safety of the battery.
[0003] Although rechargeable magnesium batteries have shown many advantages, their practical application is still out of reach. Key issues such as low operating voltage, slow kinetics, and poor cycle stability have hindered their development. The main factors include: (1) Mg 2+ The effective deposition and dissolution process in the electrolyte faces challenges. Due to its high charge density, the diffusion efficiency of magnesium ions in the electrolyte is relatively low. (2) Developing a method to achieve Mg 2+ The embedding and de-embedding of high energy density cathode materials is extremely challenging. (3) The matching problem between electrolyte and electrode. The electrochemical window of the electrolyte is narrow, which greatly limits the choice of electrode materials. (4) The passivation properties, low solubility and slow magnesium dissolution / deposition kinetics of the magnesium metal anode when in contact with the electrolyte seriously hinder the development and practical application of rechargeable magnesium batteries. Therefore, the development of a new magnesium battery electrolyte with high ionic conductivity and high magnesium metal dissolution / deposition efficiency is of great significance for the commercialization of rechargeable magnesium-ion batteries. Summary of the invention
[0004] Purpose of the invention: The present invention aims to provide an innovative magnesium-lithium composite electrolyte for a rechargeable magnesium battery and its preparation method and application. By introducing lithium salt additives, the present invention can effectively overcome the problem of slow magnesium ion kinetics and broaden the selection range of positive electrode materials. In addition, the addition of halogen ions in lithium salt additives can adjust the solvation structure of magnesium ions in the electrolyte magnesium salt at the negative electrode interface, reduce the dissolution / deposition overpotential of the magnesium negative electrode, and improve the reversibility of magnesium deposition. These improvements significantly improve the cycle stability of the battery, show excellent electrochemical performance, and effectively solve the problems existing in the prior art.
[0005] Technical solution: The magnesium-lithium composite electrolyte for a rechargeable magnesium battery provided by the present invention comprises an organic ether solvent, an electrolyte magnesium salt and a lithium salt additive, wherein the concentration of the electrolyte magnesium salt in the electrolyte is 0.01-1.0M, preferably 0.2-0.3M, and the concentration of the lithium salt additive in the electrolyte is 0.01-1.0M, preferably 0.2-0.6M.
[0006] Furthermore, the molar ratio of the electrolyte magnesium salt to the lithium salt additive is 0.5-3:1.
[0007] Furthermore, the electrolyte magnesium salt is magnesium trifluoromethanesulfonate.
[0008] Furthermore, the lithium salt additive is lithium chloride.
[0009] Furthermore, the organic ether solvent is at least one of tetrahydrofuran, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether.
[0010] Furthermore, the electrolyte is dried by adding an appropriate amount of molecular sieve before use to make its water content less than 10 ppm. Molecular sieve.
[0011] The present invention provides a method for preparing the above-mentioned magnesium-lithium composite electrolyte for a rechargeable magnesium battery, comprising the following steps: in a glove box filled with argon atmosphere, adding electrolyte magnesium salt and lithium salt additives to an organic ether solvent, and heating and stirring sufficiently to obtain the magnesium-lithium composite electrolyte for a rechargeable magnesium battery.
[0012] Furthermore, the oxygen content and moisture content of the glove box are both lower than 1 ppm; the organic ether solvent is pre-dried by molecular sieve, and the molecular sieve is Molecular sieve; the heating and stirring conditions are: heating temperature is 30-80°C, stirring speed is 300-1000r / min.
[0013] The present invention provides the application of the above-mentioned magnesium-lithium composite electrolyte for rechargeable magnesium battery in the fields of symmetrical batteries and asymmetrical batteries.
[0014] Furthermore, the symmetrical battery includes a positive electrode material, a negative electrode material, a diaphragm and a magnesium-lithium composite electrolyte for a rechargeable magnesium battery, wherein the positive electrode material is metallic magnesium or a magnesium alloy; the asymmetric battery includes a positive electrode material, a negative electrode material, a diaphragm and a magnesium-lithium composite electrolyte for a rechargeable magnesium battery, wherein the positive electrode material is aluminum, copper, molybdenum, stainless steel or titanium.
[0015] Furthermore, the negative electrode material is metal magnesium or a magnesium alloy, and the separator is at least one of a glass fiber separator, a polyethylene film, a polypropylene film or a polymer composite film.
[0016] Invention principle: The electrolyte prepared by the present invention uses organic ether solvent as a single component to dissolve magnesium salt and lithium salt. The special feature is that magnesium trifluoromethanesulfonate and lithium chloride are not easily soluble in ether solvents alone, but they can be dissolved after being mixed in a certain proportion. The obtained electrolyte not only has excellent electrochemical properties, but also has a simple preparation process without complicated pretreatment and post-treatment steps, thereby greatly reducing the production cost. These advantages enable this technology to meet the requirements of commercialization of rechargeable magnesium batteries.
[0017] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: the present invention significantly improves the diffusion kinetics of magnesium ions by adding lithium chloride to the electrolyte containing the organic ether solvent of the electrolyte magnesium salt magnesium trifluoromethanesulfonate; - The addition of Mg can also regulate 2+ The solvation structure of Mg 2+ The ionic conductive layer on the surface significantly reduces the overpotential of magnesium negative electrode dissolution / deposition, broadens the electrochemical stability window of the electrolyte, and improves the cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The dissolution conditions of the electrolytes prepared in Examples 1 to 7 and Comparative Examples 1 to 2 are shown, wherein (a) is Comparative Example 1; (b) is Comparative Example 2; (c) is Example 1; (d) is Example 2; (e) is Example 3; (f) is Example 4; (g) is Example 5; (h) is Example 6; (i) is Example 7;
[0019] Figure 2 The chronoamperometry diagram of the electrolyte prepared in Examples 1 to 6 and Comparative Example 1 is a Mg / Mg symmetric battery at an overpotential of -0.5 V within 400 s;
[0020] Figure 3 - (a) is the charge and discharge curve of the electrolyte prepared in Comparative Example 1 in a Mg / Mg symmetrical battery, with a current density of 0.05 mA cm -2 , with an area capacity of 0.025 mAh cm-2 (b) is the charge and discharge curve of the electrolyte prepared in Comparative Example 2 in a Mg / Mg symmetrical battery, with a current density of 0.1 mA cm -2 , with an area capacity of 0.05 mAh cm -2 (c) is the charge and discharge curve of the electrolyte prepared in Comparative Example 3 in a Mg / Mg symmetrical battery, with a current density of 0.01 mA cm -2 , with an area capacity of 0.005 mAh cm -2 ;
[0021] Figure 4 The charge and discharge curves of the electrolytes prepared in Examples 1 to 6 in Mg / Mg symmetric batteries, with a current density of 0.1 mA cm -2 , with an area capacity of 0.05 mAh cm -2 ;
[0022] Figure 5 The charge and discharge curves of the electrolytes prepared in Examples 1 to 6 in Mg / Mg symmetrical batteries, with a current density of 0.5 mA cm -2 , with an area capacity of 0.25 mAh cm -2 ;
[0023] Figure 6 The limiting current test results of the electrolytes prepared in Examples 1 to 6 in Mg / Mg symmetric batteries are shown;
[0024] Figure 7 The electrochemical impedance spectroscopy (EIS) diagrams of the electrolytes prepared in Examples 1 to 6 and Comparative Examples 1 to 2 before and after cycling in a Mg / Mg symmetric battery are shown in the test range of 10 6 Hz to 10 -2 Hz, amplitude 5mV;
[0025] Figure 8 Linear sweep voltammetry (LSV) diagrams of asymmetric cells composed of different research electrodes and magnesium electrodes using the electrolytes prepared in Examples 1 to 7 and Comparative Examples 1 to 2, with the scanning voltage ranging from open circuit voltage (OCV) to 6.5 V and the scanning rate being 5 mV s -1 ;
[0026] Fig. 9 Scanning electron microscope (SEM) images of the electrolytes prepared in Examples 1 to 6 after magnesium metal dissolution / deposition electrochemical testing, wherein (a) is Example 1, (b) is Example 2, (c) is Example 3, (d) is Example 4, (e) is Example 5, and (f) is Example 6;
[0027] Fig.10The charge-discharge curves and coulomb efficiency diagram of the electrolyte prepared in Example 3 in an asymmetric battery composed of different research electrodes and magnesium electrodes, with a current density of 0.5 mA cm -2 , with an area capacity of 0.25 mAh cm -2 ;
[0028] Fig.11 X-ray diffraction (XRD) patterns of the electrolytes prepared in Examples 1 to 6 and Comparative Example 1 after cycling in Mg / Mg symmetric batteries. DETAILED DESCRIPTION
[0029] The present invention is further described below in conjunction with specific embodiments and drawings.
[0030] Embodiment 1: The magnesium-lithium composite electrolyte of the rechargeable magnesium battery provided in this embodiment includes ethylene glycol dimethyl ether, magnesium trifluoromethanesulfonate and lithium chloride, wherein the concentration of magnesium trifluoromethanesulfonate in the electrolyte is 0.3M, and the concentration of lithium chloride in the electrolyte is 0.1M.
[0031] The preparation method of the above electrolyte solution comprises the following steps: the electrolyte solution is prepared in a glove box filled with argon atmosphere, and the oxygen content and moisture content of the glove box are both less than 1 ppm. 2 ) and lithium chloride (LiCl) were added to ethylene glycol dimethyl ether (DME) solvent to prepare 0.3M Mg(OTf) 2 +0.1M LiCl-DME electrolyte, fully heated and stirred to obtain the target electrolyte, the heating temperature was 45°C, and the stirring speed was 500r / min. The electrolyte was added with an appropriate amount before use Molecular sieve drying. The moisture content of the electrolyte was tested to be less than 10ppm.
[0032] Embodiment 2: The magnesium-lithium composite electrolyte of the rechargeable magnesium battery provided in this embodiment includes ethylene glycol dimethyl ether, magnesium trifluoromethanesulfonate and lithium chloride, wherein the concentration of magnesium trifluoromethanesulfonate in the electrolyte is 0.3M, and the concentration of lithium chloride in the electrolyte is 0.2M.
[0033] The preparation method of the above electrolyte solution comprises the following steps: the electrolyte solution is prepared in a glove box filled with argon atmosphere, and the oxygen content and moisture content of the glove box are both less than 1 ppm. 2 ) and lithium chloride (LiCl) were added to 0.3M Mg(OTf) in ethylene glycol dimethyl ether (DME) solvent. 2 +0.2M LiCl-DME electrolyte, fully heated and stirred to obtain the target electrolyte, the heating temperature was 45°C, and the stirring speed was 500r / min. The electrolyte was added with an appropriate amount before use Molecular sieve drying. The moisture content of the electrolyte was tested to be less than 10ppm.
[0034] Embodiment 3: The magnesium-lithium composite electrolyte of the rechargeable magnesium battery provided in this embodiment includes ethylene glycol dimethyl ether, magnesium trifluoromethanesulfonate and lithium chloride, wherein the concentration of magnesium trifluoromethanesulfonate in the electrolyte is 0.3M, and the concentration of lithium chloride in the electrolyte is 0.3M.
[0035] The preparation method of the above electrolyte solution comprises the following steps: the electrolyte solution is prepared in a glove box filled with argon atmosphere, and the oxygen content and moisture content of the glove box are both less than 1 ppm. 2 ) and lithium chloride (LiCl) were added to ethylene glycol dimethyl ether (DME) solvent to prepare 0.3M Mg(OTf) 2 +0.3M LiCl-DME electrolyte, fully heated and stirred to obtain the target electrolyte, the heating temperature was 45°C, and the stirring speed was 500r / min. The electrolyte was added with an appropriate amount before use Molecular sieve drying. The moisture content of the electrolyte was tested to be less than 10ppm.
[0036] Embodiment 4: The magnesium-lithium composite electrolyte for the rechargeable magnesium battery provided in this embodiment includes ethylene glycol dimethyl ether, magnesium trifluoromethanesulfonate and lithium chloride, wherein the concentration of magnesium trifluoromethanesulfonate in the electrolyte is 0.3M, and the concentration of lithium chloride in the electrolyte is 0.4M.
[0037] The preparation method of the above electrolyte solution comprises the following steps: the electrolyte solution is prepared in a glove box filled with argon atmosphere, and the oxygen content and moisture content of the glove box are both less than 1 ppm. 2 ) and lithium chloride (LiCl) were added to ethylene glycol dimethyl ether (DME) solvent to prepare 0.3M Mg(OTf) 2 +0.4M LiCl-DME electrolyte, fully heated and stirred to obtain the target electrolyte, the heating temperature was 60℃, and the stirring speed was 650r / min. The electrolyte was added with an appropriate amount before use Molecular sieve drying. The moisture content of the electrolyte was tested to be less than 10ppm.
[0038] Embodiment 5: The magnesium-lithium composite electrolyte of the rechargeable magnesium battery provided in this embodiment includes ethylene glycol dimethyl ether, magnesium trifluoromethanesulfonate and lithium chloride, wherein the concentration of magnesium trifluoromethanesulfonate in the electrolyte is 0.3M, and the concentration of lithium chloride in the electrolyte is 0.5M.
[0039] The preparation method of the above electrolyte solution comprises the following steps: the electrolyte solution is prepared in a glove box filled with argon atmosphere, and the oxygen content and moisture content of the glove box are both less than 1 ppm. 2) and lithium chloride (LiCl) were added to ethylene glycol dimethyl ether (DME) solvent to prepare 0.3M Mg(OTf) 2 +0.5M LiCl-DME electrolyte, fully heated and stirred to obtain the target electrolyte, the heating temperature was 60℃, and the stirring speed was 650r / min. The electrolyte was added with an appropriate amount before use Molecular sieve drying. The moisture content of the electrolyte was tested to be less than 10ppm.
[0040] Embodiment 6: The magnesium-lithium composite electrolyte for the rechargeable magnesium battery provided in this embodiment includes ethylene glycol dimethyl ether, magnesium trifluoromethanesulfonate and lithium chloride, wherein the concentration of magnesium trifluoromethanesulfonate in the electrolyte is 0.3M, and the theoretical concentration of lithium chloride in the electrolyte is 0.6M.
[0041] The preparation method of the above electrolyte solution comprises the following steps: the electrolyte solution is prepared in a glove box filled with argon atmosphere, and the oxygen content and moisture content of the glove box are both less than 1 ppm. 2 ) and lithium chloride (LiCl) were added to ethylene glycol dimethyl ether (DME) solvent to prepare a theoretical concentration of 0.3M Mg(OTf) 2 +0.6M LiCl-DME electrolyte (the actual concentration of LiCl is slightly lower than this value), after sufficient heating and stirring, a saturated electrolyte (a small amount of solid particles are not dissolved) is obtained, the heating temperature is 60°C, and the stirring speed is 650r / min. Before use, add an appropriate amount of Molecular sieve drying. The moisture content of the electrolyte was tested to be less than 10ppm.
[0042] Embodiment 7: The magnesium-lithium composite electrolyte of the rechargeable magnesium battery provided in this embodiment includes ethylene glycol dimethyl ether, magnesium trifluoromethanesulfonate and lithium chloride, wherein the concentration of magnesium trifluoromethanesulfonate in the electrolyte is 0.2M, and the concentration of lithium chloride in the electrolyte is 0.2M.
[0043] The preparation method of the above electrolyte solution comprises the following steps: the electrolyte solution is prepared in a glove box filled with argon atmosphere, and the oxygen content and moisture content of the glove box are both less than 1 ppm. 2 ) and lithium chloride (LiCl) were added to ethylene glycol dimethyl ether (DME) solvent to prepare 0.2M Mg(OTf) 2 +0.2M LiCl-DME electrolyte, fully heated and stirred to obtain the target electrolyte, the heating temperature was 45°C, and the stirring speed was 500r / min. The electrolyte was added with an appropriate amount before use Molecular sieve drying. The moisture content of the electrolyte was tested to be less than 10ppm.
[0044] Comparative Example 1: The electrolyte preparation method provided in this comparative example is: the electrolyte is prepared in a glove box filled with argon atmosphere, and the oxygen content and moisture content of the glove box are both less than 1ppm. Magnesium trifluoromethanesulfonate (Mg(OTf) 2 ) was added to ethylene glycol dimethyl ether (DME) solvent to prepare 0.03M Mg(OTf) 2 -DME blank electrolyte, after sufficient heating and stirring to obtain the comparative electrolyte, the heating temperature is 65℃, and the stirring speed is 700r / min. The electrolyte is added with an appropriate amount before use Molecular sieve drying. The moisture content of the electrolyte was tested to be less than 10ppm.
[0045] Comparative Example 2: The electrolyte preparation method provided in this comparative example is: the electrolyte is prepared in a glove box filled with argon atmosphere, and the oxygen content and moisture content of the glove box are both less than 1ppm. 2 ) was added to ethylene glycol dimethyl ether (DME) solvent to prepare saturated Mg(OTf) 2 -DME blank electrolyte (Mg(OTf) 2 The actual concentration is less than the calculated concentration 0.1M), and the comparative electrolyte (some solid particles are not dissolved) is obtained after sufficient heating and stirring. The heating temperature is 65°C and the stirring speed is 700r / min. The electrolyte is added with an appropriate amount before use Molecular sieve drying. The moisture content of the electrolyte was tested to be less than 10ppm.
[0046] Comparative Example 3: The electrolyte preparation method provided in this comparative example is: the electrolyte is prepared in a glove box filled with argon atmosphere, and the oxygen content and moisture content of the glove box are both less than 1ppm. 2 ) and lithium nitrate (LiNO 3 ) was added to ethylene glycol dimethyl ether (DME) solvent to prepare 0.2M Mg(OTf) 2 +1.0M LiNO 3 -DME electrolyte, after sufficient heating and stirring, the comparative electrolyte was obtained, the heating temperature was 45°C, and the stirring speed was 500r / min. The electrolyte was added with an appropriate amount before use Molecular sieve drying. The moisture content of the electrolyte was tested to be less than 10ppm.
[0047] The electrolytes prepared in Examples 1 to 7 and Comparative Examples 1 to 2 were subjected to performance tests. The battery performance tests were all conducted using a Blue Electric battery testing system and a Chenhua electrochemical workstation, and the physical properties were characterized using a scanning electron microscope and an X-ray diffractometer. In order to test the electrochemical properties of the electrolyte, Mg / Mg symmetric batteries and asymmetric batteries (including Mg / Al, Mg / Cu, Mg / Mo, Mg / SS, and Mg / Ti) were used respectively. The electrolytes prepared in the above embodiments were used, and the diaphragm was glass fiber. They were assembled into CR2032 button batteries, and tests such as magnesium metal dissolution / deposition, electrochemical impedance spectroscopy, linear sweep voltammetry, chronoamperometry, and asymmetric battery charge and discharge were performed. In order to characterize the morphological structure and material composition of the electrode surface after cycling, SEM and XRD test analyses were performed on the battery pole pieces after long cycles. The test results are shown in Figure 2. Figure 1-Figure 11 .
[0048] Figure 1 The dissolution of the electrolytes prepared in Examples 1 to 7 and Comparative Examples 1-2 specifically includes the following electrolytes: (a) Comparative Example 1; (b) Comparative Example 2; (c) Example 1; (d) Example 2; (e) Example 3; (f) Example 4; (g) Example 5; (h) Example 6; (i) Example 7; wherein the electrolytes corresponding to (b) and (h) contain solids and are saturated solutions. The addition of lithium chloride significantly improves the dissolution of magnesium trifluoromethanesulfonate (Mg(OTf) 2 ) in DME solvent. When the concentration of lithium chloride reaches 0.6 M, the solution is saturated, and a small amount of solid cannot be dissolved.
[0049] Figure 2 The chronoamperometry diagrams of the Mg / Mg symmetric cell at -0.5V overpotential within 400s for the electrolytes prepared in Examples 1-6 and Comparative Example 1 are shown. The test results show that at the beginning of the electrochemical reaction, the current is high, and gradually decreases over time to reach a steady state, indicating that after 50s of transient two-dimensional diffusion, the electrolyte exhibits a stable three-dimensional diffusion pattern.
[0050] Figure 3 (a) is the charge-discharge curve of the electrolyte prepared in Comparative Example 1 in a Mg / Mg symmetrical battery, with a current density of 0.05 mA cm -2 , with an area capacity of 0.025 mAh cm -2 (b) is the charge and discharge curve of the electrolyte prepared in Comparative Example 2 in a Mg / Mg symmetrical battery, with a current density of 0.1 mA cm -2 , with an area capacity of 0.05 mAh cm -2 (c) is the charge and discharge curve of the electrolyte prepared in Comparative Example 3 in a Mg / Mg symmetrical battery, with a current density of 0.01 mA cm-2 , with an area capacity of 0.005 mAh cm -2 ; The test results show that in Mg(OTf) 2 -DME blank electrolyte, the dissolution / deposition overpotential of magnesium metal is high and the stability is poor; when lithium nitrate is added to the electrolyte, the dissolution / deposition overpotential of magnesium metal is still high.
[0051] Figure 4 The charge-discharge curves and cycle stability of the magnesium negative electrode prepared in Examples 1 to 6 in the corresponding electrolytes. The test results show the effect of adding electrolytes with different concentrations of lithium chloride on the charge-discharge performance in Mg / Mg symmetric batteries. The current density of constant current charge and discharge is set to 0.1 mA cm -2 The introduction of lithium chloride significantly reduces the dissolution / deposition overpotential of magnesium metal and greatly promotes the interfacial charge transfer kinetics, indicating that this type of electrolyte has excellent electrochemical performance for magnesium metal anode.
[0052] Figure 5 The charge-discharge curves and cycle stability of the magnesium negative electrode prepared in Examples 1 to 6 in the corresponding electrolytes. The test results show the effect of adding electrolytes with different concentrations of lithium chloride on the charge-discharge performance in Mg / Mg symmetric batteries. The constant current charge-discharge current density is set to 0.5 mA cm -2 By optimizing the concentration of lithium chloride, the charge-discharge performance and cycle stability of the magnesium anode in Mg / Mg symmetric batteries can be significantly improved.
[0053] Figure 6 The limiting current test diagram of the electrolyte prepared in Example 1 to Example 6 in the Mg / Mg symmetric battery. During the test, the battery was charged and discharged for 5 times at different current densities. After the test, the battery was charged and discharged at 0.1 or 0.5 mA cm -2 The charge and discharge long cycle test was carried out at a low current density. Specifically, the current density test range of Example 1 is 0.1-1 mA cm -2 , the increase in current density is 0.1 mA cm -2 The current density test range of Example 2 is 0.1-1mAcm -2 (The increase is 0.1mAcm -2 ) and 2-3 mA cm -2 (The increase is 1mA cm -2 ); The current density test range of Example 3 is 0.1-1mA cm -2 (The increase is 0.1 mA cm -2 ) and 2-6mA cm -2 (The increase is 1mA cm -2); The current density test range of Examples 4, 5 and 6 is 0.1-1 mA cm -2 (The increase is 0.1 mA cm -2 ) and 2-7 mA cm -2 (The increase is 1mA cm -2 ).like Figure 6 As shown in (e) and (f), when 0.5M or 0.6M lithium chloride is added to the electrolyte, the -2 ), the symmetrical battery can still maintain a stable potential curve during the deposition and dissolution of magnesium, and the overpotential is kept below 1.2 V, indicating that these two concentrations of electrolyte have the characteristics of withstanding large currents.
[0054] Figure 7 The EIS graphs of the electrolytes prepared in Examples 1 to 6 and Comparative Examples 1-2 before and after cycling in Mg / Mg symmetric cells. The test results show that when lithium chloride is added to the electrolyte, its interface transfer resistance is significantly reduced, however, the ion diffusion resistance is still large. Nevertheless, the addition of lithium chloride does help reduce Mg 2+ Diffusion resistance.
[0055] Figure 8 LSV diagrams of the electrolytes prepared in Examples 1 to 7 and Comparative Examples 1-2 in asymmetric cells (Mg / Al, Mg / Cu, Mg / Mo, Mg / SS, Mg / Ti cells) with different research electrodes and magnesium electrodes. The test results show that the voltage range is OCV to 6.5V and the scan rate is 5mV s -1 Under the conditions of , the electrochemical window of the electrolyte in different working electrodes is greater than 4.0 V, indicating that this type of electrolyte has a wide electrochemical window and high oxidation stability.
[0056] Fig. 9 The SEM images of the electrolytes prepared in Examples 1 to 6 after the magnesium metal dissolution / deposition electrochemical test. The test results show that after the charge and discharge cycle, the magnesium electrode surface presents a uniform and dense magnesium deposit ( Fig. 9 (a)-(f)) in the figure indicate that this type of electrolyte has excellent electrochemical performance for magnesium metal negative electrode.
[0057] Fig.10 The charge-discharge curves and coulomb efficiency diagrams of the electrolyte prepared in Example 3 in different asymmetric batteries (Mg / Al, Mg / Cu, Mg / Mo, Mg / SS, Mg / Ti). The test results show that at 0.5 mA cm -2Under the conditions, the battery can achieve reversible dissolution-deposition cycles, and the overpotential of deposition and dissolution is low. In particular, the Mg / Cu asymmetric battery has a coulombic efficiency of up to 99.51% and a life of more than 800 hours after 500 charge and discharge cycles. The average coulombic efficiency of all tested asymmetric batteries can be maintained above 95%, and can operate stably for more than 500 cycles. These test results show that this type of electrolyte has excellent magnesium metal dissolution / deposition performance.
[0058] Fig.11 XRD diagrams of magnesium electrodes after Mg / Mg symmetric battery cycling of the electrolytes prepared in Examples 1 to 6 and Comparative Example 1. The test results show that the magnesium metal negative electrode deposit is mainly composed of elemental magnesium, and the characteristic peaks of the XRD image after battery cycling correspond to the magnesium metal PDF card, and the surface phase of the magnesium electrode does not change significantly, which has high reversibility.
Claims
1. A magnesium-lithium composite electrolyte for a rechargeable magnesium battery, characterized in that: The electrolyte comprises an organic ether solvent, an electrolyte magnesium salt and a lithium salt additive, wherein the concentration of the electrolyte magnesium salt in the electrolyte is 0.01-1.0M, and the concentration of the lithium salt additive in the electrolyte is 0.01-1.0M.
2. The magnesium-lithium composite electrolyte for a rechargeable magnesium battery according to claim 1, characterized in that: The molar ratio of the electrolyte magnesium salt to the lithium salt additive is 0.5-3:
1.
3. The magnesium-lithium composite electrolyte for a rechargeable magnesium battery according to claim 1, characterized in that: The electrolyte magnesium salt is magnesium trifluoromethanesulfonate.
4. The magnesium-lithium composite electrolyte for a rechargeable magnesium battery according to claim 1, characterized in that: The lithium salt additive is lithium chloride.
5. The magnesium-lithium composite electrolyte for a rechargeable magnesium battery according to claim 1, characterized in that: The organic ether solvent is at least one of tetrahydrofuran, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.
6. A method for preparing a magnesium-lithium composite electrolyte for a rechargeable magnesium battery according to claim 1, characterized in that: The following steps are involved: In a glove box filled with argon atmosphere, electrolyte magnesium salt and lithium salt additives are added to an organic ether solvent, and after sufficient heating and stirring, a magnesium-lithium composite electrolyte for a rechargeable magnesium battery is obtained.
7. The preparation method according to claim 6, characterized in that: The oxygen content and moisture content of the glove box are both lower than 1 ppm; the organic ether solvent is pre-dried with molecular sieves; the heating and stirring conditions are: the heating temperature is 30-80° C., and the stirring speed is 300-1000 r / min.
8. Application of the magnesium-lithium composite electrolyte for a rechargeable magnesium battery according to claim 1 in the fields of symmetrical batteries and asymmetrical batteries.
9. The use according to claim 8, characterized in that: The symmetrical battery comprises a positive electrode material, a negative electrode material, a diaphragm and a magnesium-lithium composite electrolyte for a rechargeable magnesium battery, wherein the positive electrode material is metallic magnesium or a magnesium alloy; the asymmetrical battery comprises a positive electrode material, a negative electrode material, a diaphragm and a magnesium-lithium composite electrolyte for a rechargeable magnesium battery, wherein the positive electrode material is aluminum, copper, molybdenum, stainless steel or titanium.
10. The use according to claim 9, characterized in that: The negative electrode material is metal magnesium or a magnesium alloy, and the separator is at least one of a glass fiber separator, a polyethylene film, a polypropylene film or a polymer composite film.
Citation Information
Patent Citations
Electrolyte for magnesium rechargeable battery and preparation method thereof
CN105322229A
Magnesium battery electrolyte and preparation method thereof, and magnesium battery
CN110336079A
Full inorganic salt type rechargeable magnesium battery electrolyte and preparation method thereof
CN113258138A
Magnesium secondary battery electrolyte and preparation method and application thereof
CN118352606A
Rechargeable magnesium battery composite electrolyte and preparation method and application thereof
CN119447446A
Cited By
Magnesium-sulfur battery electrolyte and preparation method and application thereof
CN120809943A